Potensi Pengembangan Rantai Industri Pariwisata Metropolitan Sarbagita (Denpasar, Badung, Tabanan, dan Gianyar) Untuk Mendukung Keberlanjutan Desa-Kota - Selfa Septiani Aulia; Salsabila Hisanah Herias; Adinda Shofia Maulida (REKA RUANG, 2022)
Sarbagita is an urban area with international standard tourism as its main economic activity. The Sarbagita Metropolitan Area consists of several areas, namely Denpasar, Badung, Gianyar and Tabanan. The Covid-19 pandemic has had an impact on the weakening of the economy and Micro, Small and Medium Enterprises or MSMEs in the tourism sector. At the time of adaptation to new habits, the concept of staycation in urban areas is related to nature tourism and cultural tourism in rural areas to develop into new opportunities in the tourism sector. The staycation concept that utilizes tourism activities to stay in a five-star hotel in an urban area has the potential to be interrelated with tourism in rural areas based on natural tourism and cultural tourism. This study aims to identify the tourism industry chain based on the analysis of the tourism supply chain and efforts to develop interrelated tourism activities in the Sarbagita Metropolitan Area. The research methodology used is qualitative and quantitative. The content analysis method is used to identify the tourism supply chain in Metropolitan Sarbagita. The development of the potential of the tourism industry chain during the normal adaptation period of the Covid-19 pandemic was carried out using a quantitative approach using analysis of tourist demand trends in the development of the tourism industry chain. The development of the tourism industry chain to support rural-urban sustainability in the Sarbagita Metropolitan Area produces 3 (three) scenarios from the supply side and the demand side, namely optimistic, moderate and pessimistic.